Inklusi-Eksklusi Aktor Sosial pada Pembentukan Opini Publik oleh Konten Artificial Intelligence TikTok: Inclusion-Exclusion of Social Actors in Public Opinion Formation via TikTok Artificial Intelligence Content - Nensilianti, Nensilianti; Sarina, Sarina; Ridwan, Ridwan (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2026)
This study aims to uncover strategies for shaping public opinion through artificial intelligence (AI)-based content on the TikTok platform, with a focus on analyzing the inclusion and exclusion of social actors using Theo van Leeuwen’s (2008) model. This study employs a descriptive qualitative approach using multimodal critical discourse analysis. The data consists of five viral TikTok videos that use AI avatars, generative text, or synthetic voices, which were deliberately selected based on the following criteria: produced by AI, having ≥100,000 views, addressing public issues, and lasting 10–60 seconds. This analysis was conducted by identifying social actors, classifying inclusion/exclusion strategies, analyzing supporting multimodal data such as visuals, audio, and text, and interpreting the implications for public opinion. The results show that all five pieces of content consistently employ suppression strategies against critical actors such as spiritual leaders, health experts, experts in AI ethics, child safety experts, and regulators. Conversely, the content involves actors who promote the logic of entertainment, efficiency, and unreflective consumption through categorization, identification, or designation. Multimodal synergy-whether through visual-auditory dissonance or excessive harmony-reinforces this strategy. The implication is that public opinion is potentially steered toward downplaying existential issues, neglecting health and safety, blind technological optimism, and the normalization of artificial authority.